The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1002/ar.23196
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Histometric Evaluation of the Liver in Astyanax Bimaculatus (Teleostei: Characidae), Exposed to Different Concentrations of an Organochlorine Insecticide

Abstract: To investigate possible morphological changes to the liver tissue of lambaris, Astyanax bimaculatus (Linnaeus, 1758), females were exposed to treatments of sublethal concentrations of the insecticide Thiodan V R for 96 hr. Treatments included three sublethal concentrations of 1.15, 2.3, and 5.6 lg L 21 of Thiodan V R and a control group without insecticide. The action of Thiodan V R at sublethal concentrations did not affect the morphological structure of the liver as a whole, but changes in isolated locations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
2
3
0
3
Order By: Relevance
“…Vacuoles were visible in the hepatocytes of the pre-extruded groups (NE, TE). These vacuoles may indicate accumulation of glycogen or fat in the hepatocytes prompted by the algae incorporation in the feeds, as noted in previous studies [74,75]. A study revealed that the vacuoles in the liver of juvenile Senegalese sole (Solea senegalensis) disappeared after 90 days of feeding of the macroalga, Ulva ohnoi [76].…”
Section: Intestinal Healthsupporting
confidence: 52%
“…Vacuoles were visible in the hepatocytes of the pre-extruded groups (NE, TE). These vacuoles may indicate accumulation of glycogen or fat in the hepatocytes prompted by the algae incorporation in the feeds, as noted in previous studies [74,75]. A study revealed that the vacuoles in the liver of juvenile Senegalese sole (Solea senegalensis) disappeared after 90 days of feeding of the macroalga, Ulva ohnoi [76].…”
Section: Intestinal Healthsupporting
confidence: 52%
“…Among the species that have been studied in this subject, we can highlight the histology of the liver of the channel catfish Ictalurus punctatus (Rafinesque, 1818), the tigerfish Hydrocynus forskahlii (Cuvier, 1819), the trout Oncorhynchus mykiss (Walbaum, 1792), the goldfish Carassius auratus (Linnaeus 1758) and the Siberian sturgeon Acipenser baerii (Brandt, 1869) (Ostaszewska et al, 2016). However, information on liver tissues in tropical freshwater systems are scarce (e.g., Bombonato, Rochel, Vicentini, & Vicentini, 2007;Faccioli, Chedid, Bombonato, Vicentini, & Vicentini, 2014;Marcon, Bazzoli, Mounteer, & Benjamin, 2015). As most of Brazilian freshwater systems are undergoing increasing pollution, especially eutrophication, there is a need for studies on this subject on eutrophic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Revisions have considered many of the 88 genera (620 species) of Characidae as "Incertaesedis", with 86 species belonging to the genus Astyanax (LIMA et al, 2003). Several papers have reported the importance of lambari to the trophic structure of Brazilian ecosystems and their reproductive behavior in the face of environmental change (PRADO et al, 2011;MARCON et al, 2015a). Lambari is of great importance to the equilibrium of the ecosystems where they occur, namely rivers of South and Central America, and they are well represented in such ecosystems in Brazilian (CARVALHO et al, 2009;WEBER et al, 2013).…”
Section: Lambarimentioning
confidence: 99%
“…Counts for each section were done in 10 randomly selected fields for each animal in both groups using a microscope equipped with a micrometer reticle (1 mm) in a 10X objective. Granulocytes associated with atretic follicles were also counted in 10 randomly selected fields using a microscope with a 40X objective (MARCON et al, 2015a).…”
Section: Histometric Analysismentioning
confidence: 99%